Site-Specific Recombination at XerC/D Sites Mediates the Formation and Resolution of Plasmid Co-integrates Carrying a blaOXA-58- and TnaphA6-Resistance Module in Acinetobacter baumannii - Cameranesi, María M.; Morán-Barrio, Jorgelina; Limansky, Adriana S.; Repizo, Guillermo D.; Viale, Alejandro M. (Frontiers in Microbiology, 2018)
Members of the genus Acinetobacter possess distinct plasmid types which provide effective platforms for the acquisition, evolution, and dissemination of antimicrobial resistance structures. Many plasmid-borne resistance structures are bordered by short DNA sequences providing potential recognition sites for the host XerC and XerD site-specific tyrosine recombinases (XerC/D-like sites). However, whether these sites are active in recombination and how they assist the mobilization of associated resistance structures is still poorly understood. Here we characterized the plasmids carried by Acinetobacter baumannii Ab242, a multidrug-resistant clinical strain belonging to the ST104 (Oxford scheme) which produces an OXA-58 carbapenem-hydrolyzing class-D -lactamase (CHDL). Plasmid sequencing and characterization of replication, stability, and adaptive modules revealed the presence in Ab242 of three novel plasmids lacking self-transferability functions which were designated pAb242_9, pAb242_12, and pAb242_25, respectively. Among them, only pAb242_25 was found to carry an adaptive module encompassing an ISAba825-blaOXA-58 arrangement accompanied by a TnaphA6 transposon, the whole structure conferring simultaneous resistance to carbapenems and aminoglycosides. Ab242 plasmids harbor several XerC/D-like sites, with most sites found in pAb242_25 located in the vicinity or within the adaptive module described above. Electrotransformation of susceptible A. nosocomialis cells with Ab242 plasmids followed by imipenem selection indicated that the transforming plasmid form was a co-integrate resulting from the fusion of pAb242_25 and pAb242_12. Further characterization by cloning and sequencing studies indicated that a XerC/D site in pAb242_25 and another in pAb242_12 provided the active sister pair for the inter-molecular site-specific recombination reaction mediating the fusion of these two plasmids. Moreover, the resulting co-integrate was found also to undergo intra-molecular resolution at the new pair of XerC/D sites generated during fusion thus regenerating the original pAb242_25 and pAb242_12 plasmids. These observations provide the first evidence indicating that XerC/D-like sites in A. baumannii plasmids can provide active pairs for site-specific recombination mediating inter-molecular fusions and intra-molecular resolutions. The overall results shed light on the evolutionary dynamics of A. baumannii plasmids and the underlying mechanisms of dissemination of genetic structures responsible for carbapenem and other antibiotics resistance among the Acinetobacter clinical population.